Muslim-Christian polemics across the Mediterranean : the splendid replies of Shihab al-Din al-Qarafi (d. 684/1285) - Sarrió Cucarella, Diego R. (The History of Christian-Muslim Relations, 2015)
In Muslim-Christian Polemics across the Mediterranean Diego R. Sarrió Cucarella provides an exposition and analysis of Shihāb al-Dīn al-Qarāfī's (d. 684/1285) Splendid Replies to Insolent Questions (al-Ajwiba al-fākhira 'an al-as'ila al-fājira). Written in response to an apology for Christianity by the Melkite Bishop of Sidon, Paul of Antioch, the Splendid Replies is among the most extensive and most important medieval Muslim refutations of Christianity, and the primary significance of this study is to provide detailed access to its argumentation and intellectual context for the first time in a western language. Moreover, the Introduction and Conclusion creatively situate the work within the challenges of modern-day Christian-Muslim dialogue.